A Systematic Approach to Identify and Characterize the Effectiveness and Safety of Novel Probiotic Strains to Control Foodborne Pathogens - Ayala, Diana I.; Cook, Peter W.; Franco, Jorge G.; Bugarel, Marie; Kottapalli, Kameswara R.; Loneragan, Guy H.; Brashears, Mindy M.; Nightingale, Kendra K. (Frontiers in Microbiology, 2019)
A total of forty-four lactic acid bacteria (LAB) strains originally isolated from cattle feces and different food sources were screened for their potential probiotic features. The antimicrobial activity of all isolates was tested by well-diffusion assay and competitive exclusion on broth against Salmonella Montevideo, Escherichia coli O157:H7 and Listeria monocytogenes strain N1-002. Thirty-eight LAB strains showed antagonistic effect against at least one of the pathogens tested in this study. Improved inhibitory effect was observed against L. monocytogenes with zones of inhibition up to 24 mm when LAB overnight cultures were used, and up to 21 mm when cell-free filtrates (CFF) were used. For E. coli O157:H7 and Salmonella maximum inhibitions of 12 mm, and 11.5 mm were observed respectively. On broth, forty-three strains reduced L. monocytogenes up to 9.06 log10 CFU/ml, forty-one reduced E. coli O157:H7 up to 0.84 log10 CFU/ml, and thirty-two reduced Salmonella up to 0.94 log10 CFU/ml 24 hours after co-inoculation. Twenty-eight LAB isolates that exhibited the highest inhibitory effect among pathogens were further analyzed to determine their antimicrobial resistance profile, adhesion potential, and cytotoxicity to Caco-2 cells. All LAB strains tested were susceptible to ampicillin, linezolid, and penicillin. Twenty-six were able to adhere to Caco-2 cells, 5 were classified as highly adhesive with >40 bacterial cells/Caco-2 cells. Low cytotoxicity percentages were observed for the candidate LAB strains with values ranging from -5 to 8%. Genotypic identification by whole genome sequencing (WGS) confirmed all as members of the LAB group; Enterococcus was the genus most frequently isolated with 21 isolates, followed by Pediococcus with 4, and Lactobacillus with 3. In this study, a systematic approach was used for the improved identification of novel LAB strains able to exert antagonistic effect against important foodborne pathogens. Our findings suggest that the selected panel of LAB probiotic strains can be used as biocontrol cultures to inhibit and/or reduce the growth of L. monocytogenes, Salmonella, and E. coli O157:H7 in different matrices, and environments.